Pregnant women & vaccines against emerging epidemic threats: Ethics guidance for preparedness, research, and response - Krubiner, Carleigh B. (2021)
Zika virus, influenza, and Ebola have called attention to the ways in which infectious disease outbreaks can severely – and at times uniquely – affect the health interests of pregnant women and their offspring. These examples also highlight the critical need to proactively consider pregnant women and their offspring in vaccine research and response efforts to combat emerging and re-emerging infectious diseases. Historically, pregnant women and their offspring have been largely excluded from research agendas and investment strategies for vaccines against epidemic threats, which in turn can lead to exclusion from future vaccine campaigns amidst outbreaks. This state of affairs is profoundly unjust to pregnant women and their offspring, and deeply problematic from the standpoint of public health. To ensure that the needs of pregnant women and their offspring are fairly addressed, new approaches to public health preparedness, vaccine research and development, and vaccine delivery are required. This Guidance offers 22 concrete recommendations that provide a roadmap for the ethically responsible, socially just, and respectful inclusion of the interests of pregnant women in the development and deployment of vaccines against emerging pathogens. The Guidance was developed by the Pregnancy Research Ethics for Vaccines, Epidemics, and New Technologies (PREVENT) Working Group – a multidisciplinary, international team of 17 experts specializing in bioethics, maternal immunization, maternal-fetal medicine, obstetrics, pediatrics, philosophy, public health, and vaccine research and policy – in consultation with a variety of external experts and stakeholders.